(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2016)
Nineteenth century Romantic nationalism viewed the nation as one entity whose members shared a common language, folklore, customs and traditions. This view of nationalism inspired the collection of folklore which served as the cultural heritage of a society. Once collected and interpreted, folklore built a grand - although often exclusive, mean and racist - narrative of the past. This article examines the social boundaries between rural peasant commoners and the Roma in Finland in the early 20th century. Using folktales from rural Finns about the Roma, this article examines how elements of everyday communication laid bare notions of social hierarchies among citizens and, simultaneously, served as political tools. Because the policy of collecting folklore only targeted majority groups of people, that is, white peasants and small landholders, their views were considered most important and more valuable. By contrast, the Roma, as outcasts from rural communities and removed from the idea of nationhood, were underrated through the narration of tales, which directed ridicule and, at times, harsh bullying at them.